Elemen Seni Bina dan Unsur Reka Bentuk Bangunan dalam Perkembangan Institusi Pendidikan Islam: Architectural Elements and Building Design Aspects in the Development of Islamic Educational Institutions - Hashim, Siti Khadijah; Ismail, Alice Sabrina (Journal of Al-Tamaddun, 2025)
This paper is focusing on identifying and understanding the attributes of Islamic educational values by delving into the definition and essence of their philosophy. The objective of this study is to portray that the philosophy of Islamic educational values has the potential to be identified through architectural elements and building design aspects, which in this study will be concentrating on Islamic educational institutions. The scope of the study will be centering on the value of syumul (comprehensive), kamil (ideal), adil (equitability) and sejagat (universality) where these attributes complement with one another. Furthermore, the identified values have been evaluated in showing significant potential to be referred as architectural design framework in designing Islamic educational building institutions as it is not only upholding the teachings of Al-Quran and Sunnah, but also moves in line with the philosophy of architecture in producing design of built environment that are friendly to the environment and people. Besides that, this study adapts a qualitative method by analyzing, explaining and examining scholars’ and academics’ paper to find out the relationship between the philospohy of Islamic educational values with the architectural elements and building design aspects under the interpretivisme paradigm with the explanation-building strategy and socio-semiotic theory. Subsequently, the analysed findings lead towards structured and informative discussiong based on the discipline of the hermeneutic cycle. Last but not least, this paper will project a conclusion on architectural design framework of Islamic educational institutions not only act as a symbol of Islamic educational values, but also plays vital components to be a guideline in amplifying the philosophy of Islamic architecture, thus strengthening the identity that highlights the essence of Islamic educational values through architectural elements and design aspects of Islamic educational buildings.